RANCANG BANGUN DAN UJICOBA PENGERING SURYA TIPE KOLEKTOR TABUNG VAKUM (EVACUATED TUBE COLLECTOR) - rambe, siti masriani; Dina, Sari Farah; Azwardi, Azwardi; Sipahutar, Edwin Harianto (Balai Riset dan Standardisasi Industri Palembang, 2018)
Research of design of solar dryer with evacuated tube collector for drying coffee bean has been done. This research is done through the stage of formulation, design, circuit and testing tools using coffee as material to be dried.Test results of a solar dryer designed then is being used for drying coffee bean (moisture content from 52.80% to 12.30%), with forced convection system which the air speed are varied of 2-6 m/sec. During the drying process, the average weather conditions are in the range 143-855 Watt / m2, ambient temperature of 28-36 °C. The air temperature in the collector are 85-192 °C and the temperature in the drying chamber are 35-78 °C. The results showed that air drying velocity is directly proportional to the drying rate and collector efficiency but inversely to drying time and specific energy consumption (SEC).